Surrogacy in France: A summary of the situation - Bonnet, Yannis (Bioethica, 2021)
Since the first law on bioethics in France in 1994, surrogacy is prohibited. With the liberalization of our society, some occidental countries accepted surrogacy under a specific legal framework. Still, France did not bend to this and always stated that surrogacy must be forbidden. However, with globalization, that facilitates fertility tourism across Europe and even further, France faced an issue with intended parents traveling abroad to have surrogacy and went back to France with children having uncertain civil status. The French legislation has been modified, taking into account all the issues that may arise. Sometimes France took the relevant initiative, but in other cases, the legal developments resulted from the pressure of international institutions. The purpose of this paper is to present a short and concise overview of the state of surrogacy in France and the steps which led to the current situation.